Pengaruh Hidroterapi dan Quadriceps Exercise Terhadap Penurunan Nyeri pada Osteoarthritis Knee - E Y Syafitri; L S Wibisono; Najizah F; Syurrahmi Syurrahmi (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Knee osteoarthritis is one of the most prevalent musculoskeletal disorders in the elderly, characterized by progressive degeneration of articular cartilage, chronic pain, joint stiffness, and reduced functional capacity. In Indonesia, the prevalence of knee osteoarthritis is notably high, affecting over 30% of individuals aged above 60 years. This condition leads to significant health burdens, impaired quality of life, and increased economic costs. Non-pharmacological management strategies such as hydrotherapy and quadriceps exercise are widely recommended to relieve pain and improve joint function. Hydrotherapy utilizes the physical properties of water including buoyancy, hydrostatic pressure, viscosity, and warmth to reduce joint loading, enhance circulation, and promote relaxation. Quadriceps exercise, on the other hand, focuses on strengthening the quadriceps muscle to stabilize the knee joint, thereby reducing pain and improving functionality. The combination of these two interventions is expected to provide greater benefits than a single modality. Research Design: This study employed a quasi-experimental design with a one-group pre-post test approach on 12 elderly respondents with knee osteoarthritis at OSF Magdalena Daemen BSB Convent. Pain was measured using the Visual Analogue Scale (VAS) before and after the intervention, which consisted of hydrotherapy and quadriceps exercise administered twice a week for four weeks. Results: The findings showed a decrease in the mean pain score from 4.42 to 3.08, with the Wilcoxon test yielding p = 0.001 (p < 0.05), indicating a significant difference in pain levels before and after the intervention. Conclusion: The combination of hydrotherapy and quadriceps exercise is effective in reducing pain in patients with knee osteoarthritis.